Anatomía y análisis cualitativo de saponinas, resinas y aceites en los órganos de Pascalia glauca (Asteraceae) - Hernández, Marcelo Paulo (2019)
Background and aims: Pascalia glauca is a toxic weed for cattle, with wide distribution in Argentina. The toxicity is produced by an atractiloside, but the species also contains other compounds such as saponins, resins and oils with toxic properties. The aims of this work were: 1- to perform a qualitative analysis of saponins in the underground (rhizomes + roots) and aerial organs during the four seasons of the year; 2- to study the anatomy of the vegetative and reproductive organs in search of secretory structures; 3- to identify resins and oils through histochemical tests. M&M: In each season of the years 2016-2017 full plants were collected. This material was used to study anatomy by conventional techniques; determine saponins and identify resins and oils by histochemical tests. Results: Saponins were found in all organs in small quantities and their content showed variability with the season of the year, a result that is expressed in terms of average values of temperature and rainfall. The secretory ducts with resins and oils were located in the rhizomes, stems, leaves and inflorescences, not in root. Conclusions: According to the results, all these compounds act as toxic during the year, principally in spring and increase in the summer-autumn period, due to the abundance of essential oils in the inflorescences, a characteristic that would indicate it as a promising species for its use in the control of agricultural pests.